2017
DOI: 10.1038/pr.2017.301
|View full text |Cite
|
Sign up to set email alerts
|

Food and nutrient intakes in young adults born preterm

Abstract: BackgroundAdults born preterm have higher levels of cardiometabolic risk factors than their term-born peers. Studies have suggested that at least those born smallest eat less healthily. We examined the association between early (<34 weeks) and late (34-36 weeks) preterm birth and diet and food preferences in adult age.MethodsParticipants of two cohort studies located in Finland completed a validated food frequency questionnaire (FFQ) at the age of 24 years to assess their usual diet and the adherence to health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Comparison between the risk of overweight/obesity and normal/underweight.Canadian-adapted HEI scores from two 24-h recalls that were adjusted for usual intake. The greater proportion of children in our cohort with poor-quality diets is concerning, yet lower quality diets have been observed in both Sharafi et al's preterm cohort when measured using the Healthy Eating Preference Index (47) and Matinolli et al's cohort of Finnish adults born preterm (n = 572, mean birth weight: 2211 g) when measured using the Recommended Finnish Diet Index(56).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Comparison between the risk of overweight/obesity and normal/underweight.Canadian-adapted HEI scores from two 24-h recalls that were adjusted for usual intake. The greater proportion of children in our cohort with poor-quality diets is concerning, yet lower quality diets have been observed in both Sharafi et al's preterm cohort when measured using the Healthy Eating Preference Index (47) and Matinolli et al's cohort of Finnish adults born preterm (n = 572, mean birth weight: 2211 g) when measured using the Recommended Finnish Diet Index(56).…”
mentioning
confidence: 60%
“…Among the few studies that measured dietary intake in children born preterm, Migraine et al reported lower fruit intake in 2-yold French children born <33 wk (n = 234), when measured using a questionnaire, compared to term-born controls (7). Similarly, lower fruit/vegetable intake was observed in a cohort of Finnish adults born VLBW (n = 166), when measured using 3-d food records and in men born early preterm (n = 87, <34 wk) when measured by food frequency questionnaire (56,57). However, neither of these studies evaluated associations with body composition or tested interactions with maternal BMI.…”
Section: Discussionmentioning
confidence: 93%
“…For office and 24 h mean systolic pressures, the differences of 1.7 and 2.7 mmHg did not reach statistical significance [15,16]. No difference was seen in nutrient intake and healthy nutrition index in adults born LPT and at term [17].…”
Section: Cardiometabolic Outcomesmentioning
confidence: 86%
“…61 A Finnish study found that premature-born young women had a less nutritious diet than women born full-term or men born either premature or full-term. 62 Another study found that young adults who were born very low-birth weight had lower consumption of fruits, vegetables, and milk products. 63 A study evaluating physical fi tness found that young adults born prematurely demonstrated lower muscular fi tness than controls.…”
Section: ■ Promote a Healthy Lifestylementioning
confidence: 99%